Efficacy and safety of the dual-layer flow-diverting stent (FRED) for the treatment of intracranial aneurysms. (25th October 2019) - Guimaraens, Leopoldo; Vivas, Elio; Saldaña, Jesus; Llibre, Juan Carlos; Gil, Alberto; Balaguer, Ernest; Rodríguez-Campello, Ana; Cuadrado-Godia, Elisa; Ois, Angel
Abstract : Purpose: To describe the efficacy and complications of treating cerebral aneurysms with the Flow Re-direction Endoluminal Device (FRED) and to identify predictors for aneurysm occlusion. Methods: A prospective observational registry including all consecutive aneurysms treated with FRED between December 2015 and July 2018 was designed in one therapeutic neuroangiography department. The primary endpoint for treatment efficacy was complete or near-complete occlusion (O'Kelly–Marotta (OKM) C–D), assessed by three-dimensional digital subtraction angiography. Major (all symptomatics) and minor complications were described and those with modified Rankin Scale scores 3–6 were considered clinically relevant. Univariate and multivariate analyses were performed to identify predictors of efficacy. Results: A total of 185 aneurysms were analyzed in 150 patients (mean age 54.3±11.5 years). Mean follow-up was 18.99±11.32 months (range 0–43). Efficacy was evaluated in 156 (84.32%) cases: 132 (84.6%) had OKM C–D occlusion, 31/47 (66%) within the first year and 101/109 (92.7%) later on. Major complications were observed in 12 (6.5%) cases: three strokes (one transient ischemic accident, two minor strokes), six intra-stent thrombosis, and three with bleeding, but only one (0.5%) was clinically relevant. Minor complications (all asymptomatic) were observed in 10 (5.4%) cases: three shortening/repositioning of stent; two arterial dissection, two arterial occlusion, and three intra-stent stenosis. Independent predictors of occlusion were immediate OKM grade B–C–D (OR 4.01, 95% CI 1.51 to 10.62), single aneurysm (OR 3.29, 95% CI 1.05 to 10.32), and small size aneurysm (OR 4.74, 95% CI 1.57 to 14.30). Conclusion: The FRED stent fully complied with efficacy and safety requirements for treatment of intracranial aneurysms. Three predictors of aneurysm occlusion were identified.